2022
DOI: 10.21462/jeltl.v7i1.782
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students' Perception of Hybrid Learning: Voices from English Language Education Students in Pandemic Era

Abstract: <em>The policy in learning has been changed by  the government since the Covid 19 cases decreased significantly in Indonesia. Therefore, the implementation of learning in this current era, especially in university level, is conducted limitedly in face to face learning mode known as Pembelajaran Tatap Muka (PTM) terbatas and online learning mode, named  Pembelajaran Jarak Jauh (PJJ). These mixed modes of learning are acclaimed as hybrid learning. This transition of learning potentially raises various perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…This discussion section is where the researcher interpreted and discussed the result of data after the findings have been conveyed before. Most undergraduate students give positive responses about the utilization of technology for online learning because it has an important role to assist teaching and learning during distance learning (Erliza and Septianingsih, 2022;Istiqomah, 2021). Moreover, as data shown in the findings, the EFL's college students responded positively to utilizing Zoom videoconferencing in improving speaking ability in the context of attitude and English speaking competence which has been verified by a huge amount of percentages in the close-ended questionnaire's result.…”
Section: Discussionmentioning
confidence: 67%
“…This discussion section is where the researcher interpreted and discussed the result of data after the findings have been conveyed before. Most undergraduate students give positive responses about the utilization of technology for online learning because it has an important role to assist teaching and learning during distance learning (Erliza and Septianingsih, 2022;Istiqomah, 2021). Moreover, as data shown in the findings, the EFL's college students responded positively to utilizing Zoom videoconferencing in improving speaking ability in the context of attitude and English speaking competence which has been verified by a huge amount of percentages in the close-ended questionnaire's result.…”
Section: Discussionmentioning
confidence: 67%
“…Based on previous studies, it was understood that hybrid learning had a large effect on the academic achievement of the students. The result of the study conducted by Erliza and Septianingsih (2022) confirmed that students had the same positive opinions toward the method and the way of teaching provided by the lecturer during hybrid learning (p.238). For this reason, the use of hybrid learning in educational environments should be encouraged and the necessary infrastructure and facilities should be provided.…”
Section: The Impact Of Online Learning Methods In the Development Of ...mentioning
confidence: 64%
“…This was expected based on Hypothesis 1 and it is in-line with other previous similar studies mentioning that university students tend to spend many hours daily on Facebook for entertainment, implying a possibly timely excessive way of its use (Junco 2012 ; Locatelli et al 2012 ; Michikyan et al 2015 ; Sun 2020 ; Tandoc Jr et al 2015 ). Also, the above finding reflects the long use of Facebook by adults during and in the aftermath of the pandemic period (Eghtesadi and Florea 2020 ; Erliza and Septianingsih 2022 ; Indriawati and Wibowo 2021 ; Raamkumar et al 2020 ; Wiederhold 2020 ). The severe modifications in many academic processes (e.g., distant meetings, presentations, and exams) that are still valid in many universities due to the different epidemiological circumstances in different countries (Bourdas and Zacharakis 2020 ; Erliza and Septianingsih 2022 ; Galanis et al 2020 ), have probably created a fertile ground for students to consider social networking sites, such as Facebook, as an integral and possibly helpful part of their daily social and academic life.…”
Section: Discussionmentioning
confidence: 90%
“…It constitutes a first attempt to depict the structure of the relationships between emotional (loneliness, resilience) and behavioral factors (intensity of Facebook use) to propose an explanatory model of university students’ tendency to make self-disclosures to unknown online friends. This is of high importance considering that in many countries several academic procedures in tertiary education still run online or in a hybrid way influencing students’ daily academic life (Erliza and Septianingsih 2022 ; Zrnić Novaković et al 2022 ). The proposed explanatory model of the present study constitutes a significant source of information and awareness for professionals of mental health, such as school, educational and/or counselling psychologists working at university campuses (Seidel et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation